Authority and Punishment: On the Ideological Basis of Punitive Attitudes towards Criminals. Issue 1 (2nd January 2016) - Gerber, Monica M.; Jackson, Jonathan
Abstract: Three explanations dominate the literature as to why people support tough sentencing of criminal offenders. The first is an instrumental perspective: people are concerned about becoming a victim of crime and they look to punishment to reduce future harm. The second is a relational perspective: people are concerned about community breakdown, and they support punishment to restore moral boundaries. The third is a psychological model based on ideological preferences: people desire conformity and authority in society, and they look to institutions to punish transgressions that threaten collective security. Building on the work of Tyler and Boeckmann(1977), we show that right-wing authoritarianism predicts both the extent to which people worry about social threats and the extent to which they support harsh punitive measures. Bridging research from political psychology and criminology, we conclude with the idea that popular punitive sentiment is grounded in an uncritical submission to authorities, an adherence to conservative moral values, and consonant concerns about collective security and cohesion.